Pengembangan Agro-Sociopreunership Berbasis Potensi Lokal Sebagai Rintisan Usaha Bersama Pedagang Buah di Wilayah Tanggul Jember - Diniyah, Marisatut; Wiyono , Andi Eko; Diniyah , Marisatut (IAI Darussalam, 2023)
Agriculture-based agro-sociopreneyrship is social service entherpreneurship in agriculture. Darungan Village,Tanggul Disctrict,Jember Regencyis an area that produces good local fruit potential and is always available in season, example of fruit that are often found in the area are mangosteen,rambutan and even durian.This lack of understanding and knowledge has caused many lost business opportunities for fruit traders in Darungan Village,Tanggul District,Jember Refency. The Purpose of this service is to develop startups together with the development of agro-sociopreneyrship so that they are sble to market properly so that partners can produce competitive products and improve the walfare of each member. Community service activities in the form of training are carried out using the socialization method discussions with the Unej community service implementation team. Service activities are carried out by outreach by explaining 2 materias,namely the formation of business Groups and Procedures for Making SKU. The result of this service is the formation of a business group with the name “Barokah Tanggul Fruit Business Group” and the management of SKU in the village. The results of the service are expected to be properly implemented to invrease the income of each member and reduce the problem of damage to fruit.